Electron microscopy of Treponema pallidum (Nichols) cultivated in tissue cultures of Sf1Ep cells. - Konishi, H (1986)
The in vitro interaction between Treponema pallidum and Sf1Ep cells during treponemal replication was investigated by using transmission electron microscopy. The Sf1Ep cells grown on Teflon-treated cover slips after 12 days of cocultivation were fixed in situ, overlaid with agar, embedded, and vertically sectioned. Large numbers of treponemes were found extracellularly not only at the upper cell surfaces but also in the narrow spaces between the cells and between the cells and the cover slips. These narrow spaces supported treponemal growth and survival, as did those at the upper cell surfaces. Although few in number, organisms were also seen in cell vacuoles either surrounded by a membrane or free in the cytoplasm. Some extracellular treponemes attached to host cells by body spirals or the terminal end and formed electron-dense layers at attachment sites. Some treponemes were often surrounded with amorphous, extracellular material which appeared to "connect" them to host cell surface. After 12 days of cocultivation, host cells showed excessive vacuolation and appeared to be damaged. This did not seem to be due to treponemal infection alone, because cells from uninfected cultures also showed similar vacuolation.